The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s13054-016-1225-5
|View full text |Cite
|
Sign up to set email alerts
|

Daily urinary urea excretion to guide intermittent hemodialysis weaning in critically ill patients

Abstract: BackgroundThere are no easily available markers of renal recovery to guide intermittent hemodialysis (IHD) weaning. The aim of this study was to identify markers for IHD weaning in critically ill patients with acute kidney injury (AKI).MethodsWe performed a retrospective single-center cohort study of patients treated with IHD for at least 7 days and four dialysis sessions for AKI between 2006 and 2011 in an intensive care unit (ICU) of a French university hospital. Blood and urinary markers were recorded on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 33 publications
0
34
0
1
Order By: Relevance
“…Daily urinary urea excretion is used less often but appears to be superior [81] . Results of an observational study conducted in 2000-2002 in 54 ICUs in 23 countries showed that a spontaneous urine output of 400 ml/day was associated with an 80.9% chance of successful liberation from RRT [80] .…”
Section: How Should Patients Be Liberated From Rrt?mentioning
confidence: 99%
See 1 more Smart Citation
“…Daily urinary urea excretion is used less often but appears to be superior [81] . Results of an observational study conducted in 2000-2002 in 54 ICUs in 23 countries showed that a spontaneous urine output of 400 ml/day was associated with an 80.9% chance of successful liberation from RRT [80] .…”
Section: How Should Patients Be Liberated From Rrt?mentioning
confidence: 99%
“…Patients in whom CRRT was discontinued successfully had better outcomes than patients who needed to be restarted on RRT. A retrospective single-center cohort study of 60 patients treated with IRRT for at least 7 days for AKI in an ICU of a French university hospital concluded that a daily urinary urea excretion greater than 1.35 mmol/kg/24 h was the best marker for weaning ICU patients with AKI from IRRT, followed by urine output greater than 8.5 ml/kg/24 h [81] . The areas under the receiver operating characteristics curves of daily urinary urea excretion and urine output were 0.96 and 0.86, respectively.…”
Section: How Should Patients Be Liberated From Rrt?mentioning
confidence: 99%
“…Five studies [11,17,[24][25][26] found that urine output at the time of cessation of CRRT was important for predicting successful CRRT discontinuation. Uchino et al [11] reported that urine output (OR 1.078/100 mL/ day) and creatinine level (OR 0.996 μmol/L) were significant predictors of successful CRRT discontinuation, and the AUROC curve values for urine output without diuretics and creatinine were 0.808 and 0.635, respectively.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Katayama et al [17] also reported that urine output (OR 1.09/100 mL/day) and creatinine level (OR 0.99 μmol/L) were significant predictors of successful CRRT, and the AUROC curve values for urine output and creatinine were 0.814 and 0.727, respectively. Aniort et al [26] found that the optimal diagnostic thresholds for intermittent hemodialysis weaning were a urine output greater than 8.5 mL/kg/24 h, urinary urea concentration greater than 148 mmol/L, and daily urea excretion greater than 1.35 mmol/kg/24 h, with accuracies of 82.1, 76.1, and 92.5% (p = 0.03), respectively. Wu et al [24] reported the following independent predictors for RRT within 30 days: a long duration of RRT (OR 1.06 day), a high SOFA score (OR 1.44 score), presence of oliguria on the day of discontinuation (OR 4.17; urine output, < 100 mL/8 h), and age > 65 years (OR 6.35).…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Recently, daily urinary urea excretion (24 h-urinary urea, 24h-UU) and daily urinary creatinine excretion (24 h-urinary creatinine, 24h-UCr) have been evaluated in 2 different single-center retrospective studies. Both have been demonstrated to be superior than other markers and 24h-UCr than 24h-UU in predicting RRT weaning success [104,105]. …”
Section: Recovery From Aki and Risk To Develop Ckdmentioning
confidence: 99%